Tropheryma whipplei-induced plastic bronchitis in children: a case report - Jin, Xuefeng; Zhang, Caiyun; Chen, Chao; Wang, Xiaoning; Dong, Jing; He, Yuanyuan; Zhang, Peng (Frontiers in Pediatrics, 2023)
This article reports a case of a 7-year-old child with severe pneumonia whose chest CT showed pulmonary consolidation, and bronchoscopy revealed plastic bronchitis. The metagenomic Next-Generation Sequencing (NGS) of the pulmonary lavage fluid suggested the infection of Tropheryma whipplei (T whipplei). The patient was treated with bronchial lavage to remove sputum plugs, intravenous azithromycin, and piperacillin-tazobactam and was discharged after eight days of hospitalization without any recurrence during follow-up. This article aims to raise clinical awareness of T whipplei infection and suggests that NGS for rare pathogens should be performed early for unexplained plastic bronchitis.